Performance Analysis of 150cc Single Cylinder Engine with Electronic Fuel Injection System - SHU LIANG, HO (IRC, 2018)
Motorcycle is the most common fleet in South East Asia countries and it contribute significant amount of emission to the environment. Most of motorcycles on the road today are fitted with carburettor, which is low efficiency, inconsistent air fuel ratio and emit more emissions. The introduction of Electronic Fuel Injector System is able to maintain the stoichiometric air-fuel ratio which leads to higher performance, cleaner combustion and higher efficiency. In this project, Yamaha 150cc with both carburettor system and Electronic Fuel Injector system are being compared in order to prove that Electronic Fuel Injection System is able to improve performance and emission in real world condition by comparing the output of both engines at certain engine speed. From the result, the fuel injected engine produces higher power output and lower emission than the carburetted model.